KUALITAS PAKAN FERMENTATIF BERBAHAN KULIT UBI KAYU DENGAN INOKULAN MEP+ UNTUK KULTUR IKAN NILA GESIT (Oreochromis niloticus L.) - Cahiadir Ali Akbar; Sukanto Sukanto; Siti Rukayah (Scripta Biologica, 2014)
Feed is a major component in fish farming. However, the relatively high price of feed is very burdensome for fish farmers. Therefore a relatively low-cost solution is needed to address that problem. The use of local materials such as bran, waste mushroom, tofu, onggok starch, and skin cassava can be utilized as an alternative to reduce the needs of imported materials. However, the local materials have constraints regarding nutrition and digestibility, so an appropriate technology is required to overcome this. Improving the quality of the feed can be done by fermentation. Fermentation works by breaking macromolecules such as carbohydrates and amino acids into micromolecules, so the absorption of feed nutrients in the fish intestines become more efficient. The use of inoculants MEP+ aimed to improve the digestibility of feed, detoxification and increased the productivity of tilapia GESIT (Oreochromis niloticus). This study aimed to determine the effect of fermentation on enhancing the quality of feed nutrients made from cassava skin chips by the application of inoculant MEP+. The study was carried out experimentally using a complete randomized design. The independent variable in this study was the type of feed. Observed dependent variable was feed quality. The main parameter measured was the proximate level. Supporting parameter was the growth of tilapia GESIT. The results showed a progressive increase in the levels of nutrients of feed fermented in each treatment. The increments were recorded in treatment A from 16.15 became 21.64, in B from 13.21 became 15.46, in C from 9.66 became 11.53, and in D from 8.34 became 9.87. This result implies that the use of MEP+ fermentation inoculants could boost the nutritional content of food, with an average of the increment value of 11-15%. The increment of nutrient contents in each treatment was also affected the weight gain of fish although no significant difference were observed.